Dual Roles of Hypoxia-Inducible Factor 1 in Acute Lung Injury: Tissue-Specific Mechanisms and Therapeutic Modulation - Junjing Jia; Yingyi Zhang; Qianying Lu; Sijia Tian; Yanmei Zhao; Haojun Fan (Cells)
Acute lung injury (ALI), a life-threatening clinical syndrome with multifactorial origins, is characterized by uncontrolled pulmonary inflammation and disrupted alveolar–capillary barrier integrity, leading to progressive hypoxemia and respiratory failure. In this hypoxic setting, hypoxia-inducible factor (HIF)-1 is activated, acting as a central regulator of the inflammatory response and reparative processes in injured lung tissue during ALI. The role of HIF-1 is distinctly dualistic; it promotes both anti-inflammatory and reparative mechanisms to a certain extent, while potentially exacerbating inflammation, thus having a complex impact on disease progression. We explore the latest understanding of the role of hypoxia/HIF-mediated inflammatory and reparative pathways in ALI and consider the potential therapeutic applications of drugs targeting these pathways for the development of innovative treatment strategies. Therefore, this review aims to guide future research and clinical applications by emphasizing HIF-1 as a key therapeutic target for ALI.